Tindak Tutur Ilokusi dalam Upacara Mangongkal Holi Suku Batak Toba - Jesiva Br Togatorop; Elmustian; Mangatur Sinaga (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2024)
This research aims to describe illocutionary speech acts in the Mangongkal Holi ceremony of the Toba Batak tribe. This type of research is qualitative research with descriptive methods. The data source for this research is three Mangongkal Holi videos on the YouTube application. The data collection method in this research uses the listen and note method, namely by listening to and recording the speech in the Mangongkal Holi video. There are three data analysis techniques for this research, namely data reduction, data presentation, and drawing conclusions. The results of this research were that four of the five types of illocutionary speech acts according to Searle were found with their respective functions, namely (1) assertive illocutionary functions stating, informing, boasting and reporting, (2) directive illocutionary functions to command, request, request, advise, forbid and invite, (3) commissive illocutionary function to offer (prayer), and (4) expressive illocutionary function to express thanks.